Firm-specific Variables and Net Interest Margin in Nepalese Banks - Lamichhane, Pitambar (Economic Review of Nepal, 2019)
This paper examines the impact of firm-specific variables on net interest margin in Nepalese commercial banks for the period 2005/06-2018/19. Secondary source data were collected through NRB and data have been analyzed using descriptive and causal comparative research design. In this paper, net interest margin is used as dependent variable and bank-specific variables such as size of assets, deposit ratio, loan ratio, and capital ratio are considered as explanatory variables. The estimated correlation results of the paper reveal that equity capital, bank loans and deposits are positively related with net interest margin of Nepalese commercial banks. Moreover, the regression results of this paper indicate that equity capital, bank lending and deposits have significant impact on net interest margin of banks. Finally, this paper concludes that bank loans and deposit have strong explanatory power to explain net interest margin as profitability in Nepalese commercial banks. Policy makers are suggested to formulate sound bank policies and to adopt effective strategies to increase the size of bank deposits as well as bank lending to maximize the profitability (net interest margin) in Nepalese commercial banks.